Tourist branding as a tool for tourist destination management - Kucheriava , Hanna (Human Geography Journal, 2021)
The article reveals the essence of tourist branding as a modern tool for managing tourist destinations. It is established that in an increasingly competitive environment in the world market of tourist services marketing means of promotion of tourist destinations allow influencing effectively the target audience, which resulted in an increase in the number of tourists and incomes from tourism. The paper examines the essence of tourist destinations, approaches to their definition provides examples of destinations in terms of the size of the territory. It is pointed out that it is the attractiveness factor that is decisive in the competition between them. It is pointed out that the attractiveness factor is the determining factor in the competition between them. Differences between the concepts of “brand of a tourist destination” and “brand of a territory” have been established. It is proved that the implementation of targeted territorial branding technologies helps to increase the attractiveness of tourist destinations for consumers of tourist services, investors, and local residents, and it influences the development of various spheres of their life. The usage of branding technologies in the tourism industry is of great importance, since it enables identifying a destination among other similar entities, emphasizing its uniqueness. It is proved that a necessary condition for positioning a tourist destination in the world tourist arena is the formation and promotion of its specific attractive image. The given examples show the successful implementation of the concept of tourist branding of the destination. The objectives of the national tourist branding of Ukraine and the country’s existing achievements in this direction have been defined. It has been proposed the stages of destination tourism branding, including the identification of competitive advantages, their assessment from the consumer’s perspective, the formation of the idea and the concept of the destination branding, the definition of ways how to promote the brand, monitoring, and evaluation of the effectiveness of the tourist destination branding, elimination of shortcomings and rebranding.